2014
DOI: 10.1155/2014/165841
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Oral Supplementation of Vitamin E, Injective Vitamin E and Selenium or Both during Late Pregnancy on Production and Reproductive Performance and Immune Function of Dairy Cows and Calves

Abstract: The object of this study was to determine the effect of prepartum supplementation of vitamin E with or without injective vitamin E and selenium (Se) on productive and reproductive performances and immune function in dairy cows. Sixty multiparous Holstein dairy cows were divided randomly into three groups at the end of gestation. Cows in each group received one of three treatments: (1) a single intramuscular (im) injection of vit. E + selenium 3 weeks prepartum; (2) daily supplementation of oral vit. E given fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…The increase in milk yield was assumed to be due to protection of mammary tissue from free radicals. The present results agreed with the results of Anwar et al, (2014), Kafilzadeh, et al, (2014), Salama et al, (2015) and Maurya et al, (2016), while the opposite trend was observed by Chatterjee (2002).…”
Section: Effect Of Vitamin E Supplementation On Milk Yieldsupporting
confidence: 93%
“…The increase in milk yield was assumed to be due to protection of mammary tissue from free radicals. The present results agreed with the results of Anwar et al, (2014), Kafilzadeh, et al, (2014), Salama et al, (2015) and Maurya et al, (2016), while the opposite trend was observed by Chatterjee (2002).…”
Section: Effect Of Vitamin E Supplementation On Milk Yieldsupporting
confidence: 93%
“…A dysregulation on the activation of these cells may lead to abortion, as well as diseases (Chatterjee, Chiasson, Bounds, & Mitchell, ). Several diseases and metabolic problems occur during the gestational period, mainly during or after calving (Persson, ), as this period is linked to immunosuppression (Kafilzadeh et al., ). Several factors are responsible for immunosuppression during gestation, such as endocrine alterations and decreased intake of nutrients involved in the antioxidant activity and biological functions of the animal (Persson, ; Kafilzadeh et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A dysregulation on the activation of these cells may lead to abortion, as well as diseases (Chatterjee, Chiasson, Bounds, & Mitchell, 2014). Several diseases and metabolic problems occur during the gestational period, mainly during or after calving (Persson, 2000), as this period is linked to immunosuppression (Kafilzadeh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Não foi encontrado diferença estatisca entre os grupos estudados nas duas avaliações (P= 0,7484 e P = 0,8180 respectivamente) na quantidade de animais prenhez. Kafilzadeh et al (2014) comparando o efeito de uma suplementação oral de vitamina E, com um suplemento injetável contento selênio e vitamina E, não encontraram diferença estatística na avliação de prenhez. Esse resultado foi semelhante ao encontrado nesse estudo.…”
Section: Perfis De Progesterona E Igf-1unclassified